Implementasi Model Pembelajaran Cooperative Learning (Jigsaw) Teknik Dasar Bulutangkis Kelas VII Sekolah Menengah Pertama Negeri 10 Kota Tegal - Ramadhan, Hudi Ilham; Sulaiman, Sulaiman (Universitas Negeri Semarang, 2023)
This research is motivated by the learning process of sports and health physical education carried out at SMP N 10 Kota Tegal which is still monotonous using the continuous lecture model, a teacher must be clever and creative in delivering material so that students understand the material provided. The purpose of this study to analyze the effect of the implementation of cooperative learning (jigsaw) learning models on class VII students of SMPN 10 Tegal City. The research used by research with a quantitative approach, the method used is a pre-experiment with a one-group pretest-posttest design, and collecting data using observation and tests. The result of the research is that the average badminton long serve pretest score is 42.22. With an average post-test score of 55.78. Meanwhile, the average badminton forehand stroke pretest score was 43.97. With an average post-test score of 55.84. Learning outcomes on long service tcount 20.603>ttable 2.040 with Sig(2.Tailed) 0.000<0.05. In the forehand lob tcount 16.836> ttable 2.040 with Sig(2.Tailed) 0.000 <0.05. It can be concluded that the hypothesis is accepted, there is a significant influence on the implementation of the cooperative learning (jigsaw) learning model for basic badminton techniques.